The Tao of Islam: Ceng Ho and the Legacy of Chinese Muslims in Pre-Modern Java - Sumanto Al Qurtuby (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
The fact that